2013
DOI: 10.1016/j.hrthm.2012.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Tachy-brady arrhythmias: The critical role of adenosine-induced sinoatrial conduction block in post-tachycardia pauses

Abstract: Background In patients with sinoatrial nodal (SAN) dysfunction, atrial pauses lasting several seconds may follow rapid atrial pacing or paroxysmal tachycardia (tachy-brady arrhythmias). Clinical studies suggest that adenosine may play an important role in SAN dysfunction, but the mechanism remains unclear. Objective To define the mechanism of SAN dysfunction induced by the combination of adenosine and tachycardia. Methods We studied the mechanism of SAN dysfunction produced by a combination of adenosine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 30 publications
6
47
0
Order By: Relevance
“…Coronary-perfused canine SAN-atrial preparations 14-17 (n=10 HF, Figure 1A) were immobilized by 10-20μM blebbistatin, 18 and stained by di-4-ANBDQBS (10-40μM). 15, 17 Adenosine (1, 10 and 100μM), non-selective adenosine receptor blocker theophylline (50μM, n=4), and a selective A1R blocker DPCPX 19 (1μM, n=4) were applied to the perfusate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Coronary-perfused canine SAN-atrial preparations 14-17 (n=10 HF, Figure 1A) were immobilized by 10-20μM blebbistatin, 18 and stained by di-4-ANBDQBS (10-40μM). 15, 17 Adenosine (1, 10 and 100μM), non-selective adenosine receptor blocker theophylline (50μM, n=4), and a selective A1R blocker DPCPX 19 (1μM, n=4) were applied to the perfusate.…”
Section: Methodsmentioning
confidence: 99%
“…15, 17 Adenosine (1, 10 and 100μM), non-selective adenosine receptor blocker theophylline (50μM, n=4), and a selective A1R blocker DPCPX 19 (1μM, n=4) were applied to the perfusate. The detailed sequential drug treatments for each canine SAN preparation are illustrated in Supplemental Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next measured corrected SAN recovery times (cSNRTs) (26) in response to different pacing rates in WT and KO SANs. cSNRT is a common clinical test to investigate SAN dysfunction (27) and is defined as the period of quiescence after rapid pacing, normalized to the pacing rate (11,26). In both WT and KO, we found that cSNRT was directly proportional to the rate of stimulation (Fig.…”
Section: Intracellular Ca During Spontaneous Bursts and Electrical Stmentioning
confidence: 99%